2022
DOI: 10.1155/2022/2390616
|View full text |Cite
|
Sign up to set email alerts
|

Application of Nanoporous Super Thermal Insulation Material in the Prevention and Control of Thermal Hazards in Deep Mining of Metal Mines

Abstract: As an important energy material, mineral resources have an important role in the rapid growth of the national economy. In recent years, with the enhancement of mining strength and the improvement of mechanized production level, the depth of mining has also increased year by year. Therefore, the number of heat hazards in deep mine mining has increased year by year, and the problem of heat loss in deep mines has become increasingly prominent, which has seriously affected the safe and efficient production of mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…This problem affects the mining of various mineral resources at different depths globally; for example, metal ores or coal mines in China [21][22][23], India [24], South Africa [25], and Poland [26,27], driving scientists to look for new solutions to combat this threat. A method for achieving this goal may be thermal insulation, the application of which was studied in [28,29].…”
Section: State Of the Artmentioning
confidence: 99%
“…This problem affects the mining of various mineral resources at different depths globally; for example, metal ores or coal mines in China [21][22][23], India [24], South Africa [25], and Poland [26,27], driving scientists to look for new solutions to combat this threat. A method for achieving this goal may be thermal insulation, the application of which was studied in [28,29].…”
Section: State Of the Artmentioning
confidence: 99%
“…Coal, as an indispensable fossil fuel for social development, has long been heavily relied upon worldwide, leading to the depletion of surface resources and the shift of coal mining to deeper levels [1,2]. Yet, as mining depth increases, the virgin rock temperature (VRT) gradually rises, leading to an increasingly prominent issue of mine heat damage [3,4]. Studies have indicated that prolonged exposure to high-temperature and high-humidity environments can result in a decline in human physical fitness, making individuals susceptible to heat-related illnesses such as heat stroke, heat halo, central nervous system disorders, and even death.…”
Section: Introductionmentioning
confidence: 99%
“…Others have studied thermal insulation materials, mainly exploring the thermal conductivity of different ratios of materials and the effectiveness of on-site thermal insulation. For instance, Xiao et al 19 utilized nanoporous superinsulation materials in deep metal mines, demonstrating that these materials effectively inhibit gas heat conduction. Specifically, when the heat source temperature is 200 °C, the coating surface temperature of the thermal insulation material (excluding aerogel) is 100 °C, resulting in a thermal insulation temperature difference of 100 °C.…”
Section: Introductionmentioning
confidence: 99%